2016
DOI: 10.1093/ageing/afw053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment with selective serotonin reuptake inhibitors in comparison to placebo in the progression of dementia: a systematic review and meta-analysis

Abstract: a small number of relatively low-powered studies showed no benefit or harm from SSRIs in terms of cognition, mood, agitation or ADLs. Large, methodologically robust studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…All the reviews suggested promising effects of SSRIs. [88][89][90] However, before embarking on large trials in these other conditions, the relevance of the neutral results of the FOCUS trial needs to be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…All the reviews suggested promising effects of SSRIs. [88][89][90] However, before embarking on large trials in these other conditions, the relevance of the neutral results of the FOCUS trial needs to be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies have claimed an association between SSRI use and lower dementia risk (Brodrick & Mathys, 2016), others have pointed out the difficulty of disentangling improved cognition as a result of ameliorated depressive symptoms, and improved cognition as a result of pharmacological intervention (Doraiswamy et al, 2003). Still others have failed to observe a relationship between antidepressant use and cognition (Carri–re et al, 2017; Jones, Joshi, Shenkin, & Mead, 2016) or have implicated SSRI use as an independent risk factor in the development of dementia (Lee, Lin, Sung, Liang, & Kao, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This pathological change has been suggested to contribute to the depressive symptoms that frequently precede the cognitive decline in patients with AD [6–8]. It is still being disputed whether antidepressive treatment of patients with AD with selective serotonin reuptake inhibitors (SSRIs) impacts on the decline of cognition in AD [9–12] or the conversion from mild cognitive impairment to AD [13]. In AD, the density of specific cortical 5‐HT receptors correlates positively to amyloid β (Aβ) pathology and negatively to cognitive performance [14], with a reduced density of the 5‐HT 4 R and 5‐HT 6 R being observed in mild cognitive impairment [15–17].…”
Section: Introductionmentioning
confidence: 99%